Challenges and opportunities of Intercultural Mediation in Health: A bibliographic review - Ruiz Hernández, Rocio; Hernández Fernández, Montserrat; Arjona Garrido, Ángeles (Revista Española de Comunicación en Salud, 2026)
Introduction: Intercultural mediation in the healthcare sector is a key tool for improving equity and quality of care in multicultural contexts. Objective: To analyze the main challenges and strengths of this profession, taking into account the various challenges it currently faces, such as prejudice, language and cultural barriers, lack of resources, ethical dilemmas, and insufficient training and professional recognition. Methods: A literature review was conducted using the Scopus, Web of Science, PubMed, and Google Scholar databases, based on a set of previously defined keywords. Results: The results show that this practice promotes more inclusive and patient-centered care, improves communication and trust between healthcare professionals and patients, and reduces health inequalities. Additionally, it strengthens social cohesion by adapting healthcare services to the needs of an increasingly diverse population. Conclusions: Intercultural mediation emerges as an essential strategy for addressing the current challenges facing healthcare systems in multicultural societies.
Keywords: Health comunication; migration; mediation; interculturality; health; healthcare